Effects of local technical monitoring on the landing stability of freestyle skiers - Chenglin, Z.; Weina, L. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Landing is the last link and the most telling witness of success or failure in freestyle skiing. For Chinese skiers, the poor landing stability was their fatal weakness of winning Olympic gold. Therefore, the purpose of this study was to examine the effects of local technical monitoring on the landing stability of freestyle skiers.